PENGARUH RENDAM AIR HANGAT DI KAKI UNTUK MENCEGAH TERJADINYA ULKUS PADA PENDERITA DIABTES MELLITUS DI DUSUN KEDUNGRINGIN DESA GIRIPURWA WONOGIRI - Yohanes Wahyu Nugroho (Jurnal Keperawatan GSH, 2020)
The prevalence of DM in Indonesia occupies the fourth position and continues to increase every year. The uncontrolled of blood sugar condition causes metabolic and vascular complications, one of the complications occured is diabetic foot which is caused by the inadequate peripheral circulation. The examination of Ankle Brachial Index (ABI) is an examination that can be used to assess the adequacy of peripheral circulation. According to the research, warm footbaths can increase the peripheral vascularization, which is expected to have an impact on the decrease of the ABI value. The aim of this research is to determine the effect of warm footbaths decrease the value of ABI. The study design used was quasy-experimetal by using the draft of pre-test post-test control group design. The populations of DM patient were in the village of Mayangan, the total sample of them were 20 respondents. The sampling tehnique used was simple random sampling. Statistical analysis used was paired t-test and independent t-test, with the significance of p <0.05 which means that H0 is rejected. The statistical test result of treatment group showed that there was an effect of ABI value before and after the soaking with the value of p = 0.000, while the result of statistical test between control group and treatment group showed the value of p = 0.005, it means that there is a different value of ABI between control group and treatment group. The conclusion of this study is the warm footbaths effects on the decrease of ABI value in patients with DM.Objective : To find out the effectiveness of soaking warm water in the feet to prevent ulcers in people with diabetes mellitus in the hamlet of Kedungringin, Giripurwa village, Wonogiri.The research design used a Quasy-experimental design with a pre-test post-test control group design. The number of samples is 10 respondents. Tehnink sampling using simple random sampling. Statistical analysis used paired t-test and independent t-test, with a significance of p <0.05, meaning that H0 was rejected.